A comprehensive review on thermochemical, biological, biochemical and hybrid conversion methods of bio-derived lignocellulosic molecules into renewable fuels. (1st September 2019) - Kumar, Gopalakrishnan; Dharmaraja, Jeyaprakash; Arvindnarayan, Sundaram; Shoban, Sutha; Bakonyi, Péter; Saratale, Ganesh Dattatray; Nemestóthy, Nándor; Bélafi–Bakó, Katalin; Yoon, Jeong–Jun; Kim, Sang–Hyoun
Graphical abstract: Highlights: Lignocellulose conversion via various technologies has documented. Influencing parameters of each pathway were analyzed and discussed. Integrative approaches towards bioenergy production has been proposed. Perspective of lignocellulosic biorefinery has been recommended. Abstract: In this review, the conversion (thermochemical, biological and hybrid) of chemical energy chiefly enclosed in biomass structures i.e. as 30–50% cellulose, 15–35% hemicellulose and 10–20% lignin into various forms of fuels/energy products is comparatively analyzed. Cellulose and hemicelluloses formulate almost ∼70% of the biomass and are definitely linked to the lignin structural units all the way through covalent and hydrogenic bonds; thereby, the structure formulated is tremendously rigid and resistive against processing. Hence, the vital confront towards the conversion of lignocellulosic biomass into important bio-yields via biorefining is to overcome this obstacle. This article gives an outlook over the major conversion technologies to produce biofuels from lignocellulosic biomass feedstock, by focusing on their typical performances. The core points outlined and argued will be the currently positioned pathways, utilizing the lignocellulosic materials to produce (bio) fuels, prospect on biomass supplies, and discussion on the impact of sustainability criteria, main influencing factors and uncertainties.